THE INFLUENCE OF PROFESSIONAL SKEPTICISM, INDEPENDENCY, COMPETENCE, AND PERSONALITY TYPE OF AUDITORS ON THEIR ABILITY TO DETECT FRAUD - LIA WIDAYANTI DWI AGUSTIN (Jurnal Ilmiah Mahasiswa FEB, 2018)
The  objective  of  this  study  is  to  assess  the  influence  of  professional skepticism,  independency,  competence,  and  personality  type  on  auditor‟s  ability to  detect  fraud.  The  data  of  this  study  was  collected  through  questionnaires distributed  to  140  convenience  sampling-wise  selected  respondents,  all  of  which are  auditors  working  in  non-big  four  public  accounting  firms  in  East  Java, resulting in 108 processible data. The analysis was conducted using Partial Least Squares  (PLS),  finding  that  auditor‟s  ability  to  detect  fraud  is  influenced  by professional skepticism, independency, and personality type and that competence does not influence the fraud detection ability. Therefore, public accounting firms should  increase  the  ability  of  their  auditors  in  detecting  various  forms  of  fraud during the audit process. This study is expected to provide considerations for the firms in placing their auditors according to their unique qualifications in order to maintain their performance.Keywords: professional skepticism, independency, competence, personality type, ability to detect fraud